Imagining Geographies of films - Aitken, Stuart C.; Dixon, Deborah P. (ERDKUNDE, 2006)
To the extent that the geographic study of film has come of age, it is important to not only tie it to disciplinary issues but also to push theoretical boundaries. Geographic concern is often lacking a critical perspective, focusing primarily on the geographic realism of films rather than how they produce meaning. Geographers needed to elaborate insights through critical spatial theories, so that our studies are not only about filmic representations of space but are also about the material conditions of lived experience and everyday social practices. With this essay, we argue for more critical film geographies. In doing so, we note how a series of traditional and emergent geographic 'primitives' - landscapes, spaces/spatialities, mobilities, scales and networks - are reappraised and push disciplinary boundaries for geography and film studies in general.